Lifecycle and generational application of automated updates to MDA EIS applications - Davis, Jon; Chang, Elizabeth (ACM, 2011)
EIS applications are complex and present significant costs and issues during upgrades which can lead user organisations to defer or abandon potential upgrades and cause them to miss out on the business benefits of the upgrade. Our ongoing development of temporal meta-data EIS applications [1] seeks to avoid or minimise the majority of these upgrade issues by standardising all update procedures to become an updated set or stream of meta-data changes that will be sequentially applied to implement each individual meta-data change in order, for all changes between the previous and current meta-data models. This update process removes the need from vendors to produce version specific update programs, and fully automates the end user’s meta-data EIS application update processes. Collision detection with third party customisations to meta-data EIS application, known as Variant Logic, will be greatly simplified as any potential conflict will be precisely identified in advance, reducing any compatibility effort for the customisations and ensuring timely availability for inclusion with the streamlined meta-data update. The effort for major EIS updates can be drastically reduced from often months down to days or less with the meta-data update process. Our ongoing development of temporal meta-data EIS applications [1] seeks to avoid or minimise the majority of these upgrade issues by standardising all update procedures to become an updated set or stream of meta-data changes that will be sequentially applied to implement each individual meta-data change in order, for all changes between the previous and current meta-data models. This update process removes the need from vendors to produce version specific update programs, and fully automates the end user’s meta-data EIS application update processes.Collision detection with third party customisations to meta-data EIS application, known as Variant Logic, will be greatly simplified as any potential conflict will be precisely identified in advance, reducing any compatibility effort for the customisations and ensuring timely availability for inclusion with the streamlined meta-data update. The effort for major EIS updates can be drastically reduced from often months down to days or less with the meta-data update process.